Learning style determination using fuzzy inference system - Rahimah, Zamir Ahmad (2019)
Car Rental Online Booking System was developed to help owners for car rental to advance their car rental business and to help student that searching for rental car more effectively. In this system, the user need to give the information about their detail and admin also need to give detail information about car. The main problem that has been identify is student need more time to find information and detail about which car rental are free to rent. The objective for this system is to develop a system that can help owners for car rental to advance their car rental business and to help student that searching for rental car more effectively. Rapid Application Development (RAD) has been chosen as methodology to develop this system. The RAD consist of four stages, first is requirement planning stage, user design stage, rapid construction stage and last is transition stage. After development of the system, client were given the user acceptance test (UAT) to ensure that all function work according to the requirement without any error. The UAT testing ensure the system have achieve the objective and able to solve the problem that happen before.